Influência das cultivares de videiras (Vitis vinifera L.) e do sistema de condução sobre a acarofauna - da Silva, Rita T. L.; Berté, Amália L. W.; Bizarro, Gabriel L.; Sulzbach, Angelica; da Silva, Vinicius L.; Ferla, Noeli J.; da Silva, Guilherme L.; Johann, Liana (Entomological Communications, 2021)
The South of Brazil is the largest producer of grapes, however this production is affected by climate and herbivores such as phytophagous mites. The aim of this work was to associate the mite fauna with the grape cultivars Chardonnay, BRS Lorena and hybrid cultivars rootstock Paulsen 1103, in trellising and espalier systems, in the municipalities of Bento Gonçalves and Garibaldi, Rio Grande do Sul State, Brazil. The cultivars were: Chardonnay trellis (Cl) Chardonnay espalier (Ce), BRS Lorena trellis (Ll), BRS Lorena espalier (Le) and the hybrid cultivars Paulsen rootstock 1103 (Pa). Monthly samplings were carried out from November 2016 to April 2017. Twenty plants per area were randomly sampled, from each plant three apical leaves were collected, apical, median and basal branches (60 leaves / area). In total, 6,865 mites belonging to seven families, 13 genera and 22 species were collected. The most abundant phytophagous belong to Tarsonemidae and Tenuipalpidae, the predators to Phytoseiidae and the generalists to Tydeidae and Iolinidae. The cultivars Lorena Ll was the greatest similarity (82.39%) among species mites, followed by Paulsen Pa (72.54%), Lorena Le (70.67%), Chardonnay Cl (31.79%) and Chardonnay Ce (31.48%). The highest dissimilarity among the cultivars occurred between Chardonnay Ce and Lorena Le (66.49%), followed by Chardonnay Ce, Chardonnay Cl (66.44%), Chardonnay Ce and Lorena Ll (61.49 %). Thus, there is homogeneity between the sampled cultivars and the conduction systems and the apical third of the leaves and the sampling period are important in determining the composition of the species.